Influence of operating conditions in the hydrogen production by steam reforming of methanol: numerical approach - Leonardo Esteban Pacheco Sandoval; Carlos Alirio Díaz González; Luis Eduardo Jaimes Reatiga; Leidy Juliana Carrillo; Brayan Andrés Díaz Joven (Revista Colombiana de Computación, 2017)
This work describes the unidimensional study of steam reforming of methanol at short pseudo-contact time. Steam reforming process (SRP) is important to hydrogen production as energetic vector. A compressible mathematical model 1-D is developed. Peppley kinetic mechanism (1999) is adopted. The numerical predictions show up the same trend as the experimental ones. A sensitivity analysis of the significant variables of the process is carried out (pressure, CH3OH/H2O ratio and temperature).